The challenges faced by AKIJ resources in implementing standardized job analysis process in their business practices - Bhuiyan, MD Mahim Hossain (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.